Prevalensi dan Intensitas Larva Infektif Nematoda Gastrointestinal Strongylida dan Rhabditida pada Kultur Feses kambing (Capra sp.) di Tempat Pemotongan Hewan Kambing Pontianak - Ari Hepi Yanti, Varla Dhewiyanty, Tri Rima Setyawati (Universitas Tanjungpura, 2015)
Gastrointestinal nematodes of Strongylida and Rhabditida orders are mostly found infect ruminants and may cause sufficient loss for the stock farmers. The aim of this research was to determine the prevalence and intensity of gastrointestinal nematodes infective larvae of Strongylida and Rhabditida orders in faecescultures of goat (Capra sp.) collected from four goats slaughterhouses in Pontianak. There were 30 faeces samples cultured, representing 30 individuals of goat. Faeces samples were cultured for 14 days under room temperature, the larvae then filtered using Baermann Method. The result shows that there are 3 varieties of goat slaughtered at four goat slaughterhouses in Pontianak, which are kambing kacang, Peranakan Etawa (PE), and Jawa Randu. Infective larvae of Oesophagostomum are dominantly found in faeces culture ofkambing kacang variety with prevalence value 70.83% and intensity value 40.82 larvae/gram/individuals. Infective larvae of Trichostrongylus are dominantly found in faeces culture of PE variety with prevalence value 75% and intensity value 41.33 larvae/gram/individuals. Infective larvae of Oesophagostomum are dominantly found in faeces culture of Jawa Randu variety with prevalence value 50% and intensity value 12 larvae/gram/individuals. Teladorsagia larvae are found in faeces culture of every goat varieties with the low intensity value.